Consumer Satisfaction Aligns With Price Product Quality and Service Quality: Kepuasan Konsumen Selaras Dengan Harga Kualitas Produk dan Pelayanan - Syafati Nadya; Komang Sudarsana; Made Dwipa Negara (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Customer satisfaction is essential for maintaining competitiveness in culinary businesses. Specific Background: This study focuses on a coastal seafood restaurant where consumer satisfaction is linked to price, product quality, and service quality. Knowledge Gap: Limited empirical attention has addressed these three factors in seafood restaurants with coastal dining characteristics and fluctuating consumer visits. Aims: This study analyzes the partial and simultaneous relationships between price, product quality, service quality, and customer satisfaction. Results: Based on data from 40 purposively selected respondents and SPSS analysis, price, product quality, and service quality showed positive and significant relationships with customer satisfaction, both partially and simultaneously. Novelty: The study offers empirical evidence from a coastal seafood culinary setting. Implications: Restaurant managers should maintain suitable pricing, fresh and consistent food quality, and responsive service to strengthen customer satisfaction. Highlights • Each predictor showed a significant positive partial relationship.• The combined statistical model produced a significant simultaneous result.• Freshness, taste, hygiene, consistency, and responsiveness require managerial priority. Keywords Consumer Satisfaction; Price; Product Quality; Service Quality; Coastal Culinary